Scalable carbon black deposited fabric/hydrogel composites for affordable solar-driven water purification. (20th April 2022) - Guo, Ying; Li, Congqi; Wei, Peiling; Hou, Kai; Zhu, Meifang
Highlights: l. Bilayer fabric/hydrogel composites exhibit tough interfacial bonding. 2. The hydrogel substrate combines high mechanical strength and water absorption. 3. The composites function well as effective interfacial evaporator for water purification. Abstract: Interfacial solar-driven evaporators have presented great potential for water purification owing to their low energy consumption and high steam generation efficiency. However, their further applications are hindered by the high costs and complicated fabrication processes. Here, a scalable bilayer interfacial evaporator was constructed via an affordable technique, in which carbon black deposited nonwoven fabric (CB@NF) was employed as the upper photothermal layer, as well as PVA/starch hybrid hydrogel for self-floating and water transport. Under simulated one sun irradiation, CB@NF layer displayed excellent photothermal conversion performance, whose temperature could increase 30.4 °C within 15 min. Moreover, the introduction of starch into PVA endowed the hybrid hydrogels with considerable water-absorption capability on the premise of ensuring mechanical properties. The resultant CB@NF/PVA/starch composites achieved superior interfacial adhesion performance with interfacial toughness at about 200 J m −2 . Combining with good evaporation performance, salt-rejection property and high purification efficiency on pollutants, this evaporation system would become a promising candidate to alleviate water shortage. Graphical abstract: Image, graphical abstract